New evidence for self‐medication in bonobos: Manniophyton fulvum leaf‐ and stemstrip‐swallowing from LuiKotale, Salonga National Park, DR Congo. Issue 2 (30th September 2013) - Fruth, Barbara; Ikombe, Nono Bondjengo; Matshimba, Gaby Kitengie; Metzger, Sonja; Muganza, Désiré Musuyu; Mundry, Roger; Fowler, Andrew
<x xml:space="preserve">Abstract</x> The swallowing of entire leaves by apes across Africa without chewing has been observed for over 40 plant species. Here we add evidence for (a) a new site, LuiKotale where leaf‐swallowing of Manniophyton fulvum (Euphorbiaceae) is observed in bonobos, (b) a so far unreported ingestion of unchewed stemstrips of M. fulvum, we name stemstrip‐swallowing; and (c) a test of some of the requirements put forward by Huffman for the assessment of plants ingested for medical purpose. As ecological correlates we analyzed M. fulvum phenological data and examined 1, 094 dung piles collected between 2002 and 2009. By that we assessed availability and choice of leaves. In addition, we provide the first full description of the behavior related to this plant species' use by chimpanzees or bonobos using 56 bouts of M. fulvum ingestion observed between October 2007 and February 2010. With these data we tested and met 4 of the 6 requirements given by Huffman, supporting ingestion of this species as self‐medication. Despite species' year‐round availability and abundance, M. fulvum was ingested only at specific times, in very small amounts, and by a small proportion of individuals per party. In the absence of our own parasitological data, we used M. fulvum swallowing as evidence for parasite infestation, and seasonality as a proxy for stressors underlying seasonal fluctuation and impacting immune responses. Using these indirect factors available, we investigated conditions for a parasite to develop to its infective stage as well as conditions for the host to cope with infections. Both rain and temperature were good predictors for M. fulvum ingestion. We discuss the use of M. fulvum with respect to its hispidity and subsequent purging properties and provide insight into its ethnomedicinal uses by humans, stimulating speculations about potentially additional pharmacological effects. Am. J. Primatol. 76:146–158, 2014. © 2013 Wiley Periodicals, Inc.